Tourism Marketing Strategy With The Bas Approach (Branding, Advertising And Selling) Lubuk Resam Tourist Destination, Seluma District, Bengkulu Province, An Efforts To Increase The Number Of Visitors - Putra, Delfan Eko (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
In Indonesia there are many unique and fun tourist attractions to visit, this fact influences foreign and domestic tourists to visit and vacation. Digital technology is a new trend for every individual. Opportunity to access at any time, can be accessed anywhere, and fast access time is a big attraction of digital technology. Digital and electronic technology as the main data, changes human activities, from traditional processes to interactions to internet networks. because the use of digital technology, such as social media is considered a human connector through the form of an interface, and becomes an important facility in interaction. digital media as a means of communication as well as a means to promote the potential of tourist areas, because the government's attention is still minimal in managing and seeing new tourism potential. In an effort to increase marketing and reach target markets through digital marketing, companies need to use online information dissemination and sales promotion tools, such as using social media and websites, these are digital information dissemination tools that can be accessed by the entire world community so that the dissemination of information and sales promotions can be conveyed properly. In this study, researchers are interested in the activities of tourism-aware communities utilizing digital media, especially social media in an effort to promote the tourism potential of Lubuk Resam in Seluma Regency towards Seluma Alap and Seluma Berbudaya. The methodology in this study is a descriptive analysis method with data collection techniques through interviews, observations and desk studies.